“I look at the destruction, what crop, but after all, nothing in my heart didn`t go to waste” — Poetic Flashbacks of Jan Lechoń - Urbańska, Monika (Starość i młodość w literaturze i kulturze, 2016)
First volume of Jan Lechoń poetry appears in print when he was 13. It surprises its maturity anddepth. The young poet reached the common motives of decadent sadness and doubt, but spiritual loneliness,interest of existential themes were not typical for teenager.Karmazynowy poemat was received as a literary revelation. Lechoń reaches literary perfection asa young man, so all the adult life he efforts to remain poetic laurel.As a mature creator he glanced at his reflection in the mirror, not only to seek the passage of himself,but also to examine his conscience to settle with the past. At the end of his life, Lechoń was convinced“it is all over”. His poems from this period says about longing for the lost homeland. Inner conflict ofpoet balancing between memories of his youth and terrifying death wish was his characteristics lifelongfeature. Premature maturity and tragic death seemed to be his destiny — each lived year of Lechoń’s lifecan be considered as a temporary postponement of death heppened to him on New York pavement ontragic Friday afternoon in June 1956.